Cesarean Section or Natural Childbirth? Cesarean Birth May Damage Your Health - Chen, Hongyan; Tan, Dingliang (Frontiers in Psychology, 2019)
The increasing popularity of Caesarean birth has become a social concern in many countries. This paper reviews the literature on the effects of Caesarean section on children’s psychological health. The results show that Caesarean birth may have adverse effects on children’s sensory perception, sensory integration ability, neuropsychiatric development, and the infant-mother relationship. However, there remain deficiencies in extant research methods, research content, subject groupings, and interpretation of research results. Future research should improve research methods, broaden the research content, and refine the grouping of children born by Caesarean section. The exploration of neural mechanisms is also needed, as well as research directed toward suggesting effective intervention to reduce unnecessary Caesarean sections.